Are the lakes and rivers in Dhaka city safe for recreational water activities? - Nini, Urmi Nishat (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.